Proceeding of the 44th ACM Technical Symposium on Computer Science Education 2013
DOI: 10.1145/2445196.2445370
|View full text |Cite
|
Sign up to set email alerts
|

CS circles

Abstract: Computer Science Circles is a free programming website for beginners that is designed to be fun, easy to use, and accessible to the broadest possible audience. We teach Python since it is simple yet powerful, and the course content is well-structured but written in plain language. The website has over one hundred exercises in thirty lesson pages, plus special features to help teachers support their students. It is available in both English and French. We discuss the philosophy behind the course and its design,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This simplifies the framework implementation, as most people are familiar with MS Excel. MS Excel appears to be a ubiquitous tool for data analysis and does not appear to "intimidate" users the way that some more efficient computational tools, e.g., MATLAB, Python, may (e.g., [43][44][45]). As such, the authors felt that MS Excel would be most accessible for SMCB owner-operators.…”
Section: Objectivementioning
confidence: 99%
“…This simplifies the framework implementation, as most people are familiar with MS Excel. MS Excel appears to be a ubiquitous tool for data analysis and does not appear to "intimidate" users the way that some more efficient computational tools, e.g., MATLAB, Python, may (e.g., [43][44][45]). As such, the authors felt that MS Excel would be most accessible for SMCB owner-operators.…”
Section: Objectivementioning
confidence: 99%
“…Mastering programming skills requires extensive practice and making mistakes [15]. Many MOOC websites, such as Codecademy and Khan Academy, integrate tutorials with extensive exercises using code editors with feedback systems [16]. Empirical studies show that students who learn programming interactively through welldesigned computer systems can achieve good learning outcomes and higher selfefficacy [10], [12].…”
Section: Learning From Interactive Computer Tutorsmentioning
confidence: 99%
“…More recent work by Staubitz et al proposed five requirements for an ICT to deliver programming courses: Versatility (support multiple programming languages), Novice-Friendliness (UI catered for beginners), Scalability (support for many users), Security (secure students' submissions/assessments), and Interoperability (integrate into existing infrastructures) [18]. Pritchard & Vasiga summarized that built-in coding environments are beneficial for students' continuity in learning-by-doing [16]. While most educators will agree that a mentor is essential in the initial learning process for beginners, Liyanagunawardena et al showed that in an online course, the learners' community itself can act as a mentor and could possibly mitigate the issue of not having enough teachers for students [19].…”
Section: Learning From Interactive Computer Tutorsmentioning
confidence: 99%
“…It is publicly available for free, and we also use it in our classes. The system software is based on Computer Science Circles (CS Circles) , an open‐source interactive platform for learning Python. We have extended and built upon its infrastructure.…”
Section: Introductionmentioning
confidence: 99%